A Smartphone App-Based Lifestyle Change Program for Prediabetes (D'LITE Study) in a Multiethnic Asian Population: A Randomized Controlled Trial - Lim, Su Lin; Ong, Kai Wen; Johal, Jolyn; Han, Chad Yixian; Yap, Qai Ven; Chan, Yiong Huak; Zhang, Zhi Peng; Chandra, Cheryl Christine; Thiagarajah, Anandan Gerard; Khoo, Chin Meng (Frontiers in Nutrition, 2022)
Introduction: Landmark studies have established that lifestyle interventions focused on weight loss, diet modification and physical activity can prevent diabetes progression. However, the effectiveness of mobile health application among Asians with prediabetes remains largely unexamined. We aimed to assess whether a smartphone app-based lifestyle intervention programme would lead to weight loss, normoglycemia and improved metabolic indices in a multiethnic Asian population with prediabetes. Research Design and Methods: This multicentre prediabetes RCT is part of the Diabetes Lifestyle Intervention using Technology Empowerment (D’LITE) trial. Adults (n = 148) with prediabetes and BMI ≥23 kg/m2 were randomly allocated either to the intervention group (n=72) empowered by self-monitoring features of the Nutritionist Buddy Diabetes app with in-app dietitian coaching for 6 months, or the control group (n=76) receiving standard diet counselling at baseline. Primary outcome was defined as change in body weight at 6 months, while secondary outcomes included glycemic control and other metabolic indices analysed using Generalized Linear Mixed Model analysis with intention-to-treat approach. Results: Intervention group achieved a significantly greater weight loss of 4.2 kg vs 1.3 kg (mean difference of -3.1 kg [95% CI -4.5 to -1.7], p < 0.001), and a 4.3 fold increased likelihood of achieving ≥ 5% weight loss, as compared to the control group at 6 months. The likelihood of achieving normoglycemia (defined as HbA1c < 5.7%) was 2.1 times higher in intervention group than in the control group (p < 0.018). Changes to blood pressure, total and LDL cholesterol were not statistically significant. Conclusion: An app-based lifestyle programme led to clinically significant weight loss and improved glycemia, and can potentially augment current standard care in the prevention of diabetes among an Asian multiethnic population. Clinical Trial Registration No: ACTRN12617001112358, anzctr.org.au